Using critical incident technique to identify the effect of servicescape failure and the effectiveness of recovery strategy on dining experience - Chua, Bee Lia; Boo, Huey Chern; Ab Karim, M. Shahrim; Othman, Mohhidin; Ramachandran, Sridar (Protect Print Sdn Bhd, 2010)
Despite the acknowledged importance of servicescapes, there is a dearth of empirical investigations of servicescape failures and recovery strategies and how these influence the subsequent behaviour of customers. Using the Critical Incident Technique (CIT), a total of 102 incidents had been gathered by personal interviews. The initial result revealed that cleanliness issues were the most common problem occurring in food service industries, followed by design issues, mechanical issues and social issues. Customers exhibited negative reactions to those failures and led to displays of various behaviours. The implemented recoveries were perceived both positively and negatively by the customers.